Depresi Dengan Fungsi Kognitif Pada Penderita Diabetes Mellitus Tipe II Di Wilayah Binaan Puskesmas Sedayu 2 Bantul - Essy Sekar Safitri; Brune Indah Yulitasari; Mulyanti Mulyanti (Tribhuwana Tunggadewi University, 2022)
Type II Diabetes Mellitus is a chronic disease and is an important health problem in Indonesia and the world. Type II Diabetes Mellitus is a group of metabolic diseases with hyperglycemia resulting from defects in insulin secretion and insulin action. Type II Diabetes Mellitus can affect physical and psychological health. Physical decline in type II Diabetes Mellitus sufferers causes a person to experience a decrease in cognitive and psychosocial functions, such as depression. The aim of the study was to determine the relationship between depression and cognitive function in patients with type II diabetes mellitus in the target area of the Sedayu 2 Health Center, Bantul. This type of research is a quantitative correlation study with a cross-sectional approach. The population in this study were respondents with type II Diabetes Mellitus aged ≥45 years using simple random sampling technique with a total of 110 samples. The instrument used in the depression level study used the BDI (Beck Depression Inventory) questionnaire and cognitive function used the MMSE (Mini Mental State Exam). The results of the analysis with the Kendal Tau correlation test showed that there was a significant relationship between depression and cognitive function P-value = 0.000 (p 0.05). The higher the level of depression, the more severe the cognitive function of type II Diabetes Mellitus sufferers.